PENGARUH MODAL KERJA, PENJUALAN, DAN HUTANG TERHADAP LIKUIDITAS PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 - 2018 - MARDIAH HASANAH NASUTION (JURNAL ILMIAH KOHESI, 2021)
This study aims to determine the influence of working capital, sales, and debt on liquidity in Consumer Goods companieslisted on the Indonesia Stock Exchange for the period 2014-2018. Samples were taken using purposive sampling method.The population in this study are all consumer goods sector manufacturing companies that have been and are still listed onthe Indonesia Stock Exchange for the period 2014-2018. From a population of 34 companies obtained 20 manufacturingcompanies in the consumer goods sector as a sample with an observation period of 5 years (2014-2018). The data wereanalyzed using multiple linear regressions. Based on the data analysis, it was concluded that working capital has a positiveand significant effect on the current ratio with a calculated t value of 2,537 and a significance of 0.000, so that the firsthypothesis is accepted. Sales have a positive effect and significance to the current ratio with a calculated t value of 1,978and a significance of 0.000, so that the second hypothesis is accepted. Total debt had no effect on the current ratio with acalculated t-value of -0.233 and a significance of 0.816, so the third hypothesis was rejected. The model conformity testresults show that simultaneously working capital, sales and total debt affect the current ratio. This is indicated by a calculatedF value of 4,829 and a significance value of 0.000. Adjusted R2 value of 0.604 indicates that working capital, sales and totaldebt to current ratio of 60.4% and the remaining 39.6% are explained by other variables not studied in this study.